Study on residual tensile strength of carbon fiber composite laminates after drilling - YU Fen; CUI NaiWei; HE ZhenPeng; LI BaiChun (Jixie qiangdu)
The tensile residual strength is an important mechanical property of composite laminates and plays a key role in the service life of the product. In order to study the influence of drilling process parameters on the tensile residual strength of carbon fiber composite laminates after drilling, Vumat subroutine was written with the selected failure criteria and stiffness degradation mode, and the finite element model of tensile of carbon fiber composite laminates after drilling was established in Abaqus software. The effect of spindle speed, feed rate and bit tip angle on the tensile residual strength of carbon fiber composite laminates after drilling were investigated by the orthogonal test. The results show that spindle speed, feed rate and bit tip angle all have significant effects on the laminate's tensile residual strength. Increasing spindle speed and decreasing feed rate and bit tip angle can effectively improve the laminate tensile residual strength after drilling, which provides a reference for practical processing.